PENINGKATAN SELF REGULATED LEARNING MAHASISWA DI ERA DIGITAL MELALUI PEMBELAJARAN BLENDED LEARNING (Universitas Dr. Soetomo, 2017)
Some students have not shown the ability to regulate themselves (self regulated learning) about how to learn. This is part of the impact of conventional learning. Blended learning is a learning model that is widely developed in college. This model provides opportunities for students to learn actively by self-regulation, self-control, self-motivation, and develop self-confidence, and choose or manage their own learning environment to support the effectiveness of learning. This study is based on literature review. Based on some empirical studies, it is concluded that the application of this model can improve self regulated learning learners. Keywords: blended learning, self regulated learning, conventional learning